Analisis Budaya Organisasi Dalam Meningkatkan Kinerja Karyawan Pada Badan Pusat Statistik Karawang - Lucky Hasim; Enjang Suherman (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research discusses the influence of organizational culture on employee performance at the Karawang Central Bureau of Statistics. The interview results show that a strong and positive organizational culture has increased the quantity and quality of work, responsibility, cooperation, and initiative of employees. A culture of cooperation and good communication also plays an important role in improving performance. The data analysis method used includes data reduction, data presentation, and conclusion drawing. A strong organizational culture at BPS Karawang emphasizes efficiency, productivity, responsibility, cooperation, and initiative, as well as evaluation and constructive feedback to improve work quality. Suggestions for strengthening organizational culture include improving training, evaluation systems, communication, initiative, and employee responsibility.